2016
DOI: 10.1177/2473011416s00004
|View full text |Cite
|
Sign up to set email alerts
|

3-D CT Analysis of Screw and Suture-Button Fixation for Syndesmosis Repair

Abstract: Introduction/Purpose: Historically, unstable injuries to the distal tibiofibular syndesmosis have been repaired with syndesmotic screws. However, newer repair techniques with inherently flexible implants, including suture-button constructs, may be less susceptible to malreduction and more reliably restore the native anatomy. The purpose of this study was to compare the anatomic accuracy of reduction between a syndesmotic screw and suture-button constructs for syndesmosis repair using a preinjury and postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In contrast to these, we found a mild diastasis in mean (0.2 mm) in both SYS and SBS stabilization. Also, our results confirmed that stabilization with SYS or SBS provided comparable results analyzed with 3D measurements [ 30 ]. In contrast to these 3D results, studies with two-dimensional measurements have reported a significant difference between SYS and SBS, with increased clear space in SYS in sense of diastasis of the syndesmosis [ 10 , 23 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In contrast to these, we found a mild diastasis in mean (0.2 mm) in both SYS and SBS stabilization. Also, our results confirmed that stabilization with SYS or SBS provided comparable results analyzed with 3D measurements [ 30 ]. In contrast to these 3D results, studies with two-dimensional measurements have reported a significant difference between SYS and SBS, with increased clear space in SYS in sense of diastasis of the syndesmosis [ 10 , 23 ].…”
Section: Discussionsupporting
confidence: 86%
“…Currently, there are few cadaver studies evaluating the outcome after stabilization of the syndesmosis using 3D-based measurement methods [ 30 , 32 ]. In contrast to these, we found a mild diastasis in mean (0.2 mm) in both SYS and SBS stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation